2011
DOI: 10.4028/www.scientific.net/amr.268-270.372
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Concrete Mix Proportions Centered on Performance after Exposure to High Temperature

Abstract: This paper presents the results of an experimental and statistical study on the effect of high temperatures on the retained mechanical properties of high-strength concretes (HSC). The mechanical properties of HSC significantly change during and later than exposure to elevated temperature. The compressive and splitting tensile strength of more than 400 HSC cylindrical specimens with sixteen mix proportion have investigated to study the effect of mix proportion on the retained mechanical properties of HSC specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…33,34 The mechanical properties of NSC tested at elevated temperatures or after exposure to elevated temperatures has been investigated by numerous researchers. 27,31,[35][36][37][38][39][40][41] Exposure to temperatures between 121 C and 149 C are reported by some researchers to positively affect the mechanical properties of concrete. 42 However, all previous studies have demonstrated that exposing concrete to higher temperatures leads to a significant reduction in its residual post-fire compressive and tensile strengths as wells as its modulus of elasticity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 The mechanical properties of NSC tested at elevated temperatures or after exposure to elevated temperatures has been investigated by numerous researchers. 27,31,[35][36][37][38][39][40][41] Exposure to temperatures between 121 C and 149 C are reported by some researchers to positively affect the mechanical properties of concrete. 42 However, all previous studies have demonstrated that exposing concrete to higher temperatures leads to a significant reduction in its residual post-fire compressive and tensile strengths as wells as its modulus of elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of NSC tested at elevated temperatures or after exposure to elevated temperatures has been investigated by numerous researchers 27,31,35–41 . Exposure to temperatures between 121°C and 149°C are reported by some researchers to positively affect the mechanical properties of concrete 42 .…”
Section: Introductionmentioning
confidence: 99%